2011
DOI: 10.1007/s11665-010-9786-y
|View full text |Cite
|
Sign up to set email alerts
|

Filament-Level Modeling of Aramid-Based High-Performance Structural Materials

Abstract: Molecular statics and molecular dynamics are employed to study the effects of various microstructural and topological defects (e.g., chain ends, axial chain misalignment, inorganic solvent impurities, and sheet stacking faults) on the strength, ductility, and stiffness of p-phenylene terephthalamide (PPTA) fibers/ filaments. These fibers can be considered as prototypes for advanced high strength/high-stiffness fibers like Kevlar Ò , Twaron Ò , New Star Ò , etc. While modeling these fibers, it was taken into ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 13 publications
(5 reference statements)
1
64
0
Order By: Relevance
“…Grujicic et al 56,[62][63][64][65] reported that defect's type, size and concentration are sensitive functions of the PPTA fiber fabrication (polymer synthesis, dope preparation and spinning process) -which are summarized in the present review in section 2.…”
Section: Structural Defectsmentioning
confidence: 95%
See 1 more Smart Citation
“…Grujicic et al 56,[62][63][64][65] reported that defect's type, size and concentration are sensitive functions of the PPTA fiber fabrication (polymer synthesis, dope preparation and spinning process) -which are summarized in the present review in section 2.…”
Section: Structural Defectsmentioning
confidence: 95%
“…An outstanding analysis of PPTA fibers at multi scale levels is investigated by Grujicic et al 56,[62][63][64][65] . The computational investigations properly described the material models which are used to achieve the material (PPTA) behaviour at the length-scale levels from chemical structure (atoms) to composite structure (laminate) with brief description in eight levels.…”
Section: Ppta Computational Modellingmentioning
confidence: 99%
“…The effect of AC and TC deformation modes on the fiber tensile failure strength has not been studied extensively. There are few atomistic simulations studies [20][21][22][23][24][25] that focused on the elastic and strength properties of Kevlar ® and PE crystal. Rutledge et al [20] have determined the elastic properties of Kevlar ® crystal through atomistic simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Rutledge et al [20] have determined the elastic properties of Kevlar ® crystal through atomistic simulations. Grujicic et al [21,22] studied the properties of Kevlar ® filament using non-reactive force field COMPASS (Condensed-phase Optimized Molecular Potentials for Atomistic Simulation Studies) [26]. In one study [21], they investigated the effects of microstructural and topological defects such as chain ends, inorganic-solvent impurities, chain misalignments, and sheet stacking faults on the strength, ductility, and stiffness of PPTA filament.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation